PERAN SISTEM PERADILAN DAN KEBIJAKAN KESEHATAN DALAM MENANGANI KASUS PENYALAHGUNAAN OBAT TERLARANG: STUDI TENTANG PENEGAKAN HUKUM, REHABILITASI, DAN PEMULIHAN KESEHATAN MENTAL DAN FISIK PENYALAHGUNA NARKOBA DI INDONESIA - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2025)
Illegal drug abuse in Indonesia is a complex national problem because it involves legal, health, social, and moral dimensions of society. This study aims to analyse the role of the judicial system and health policies in handling drug abuse cases through law enforcement, rehabilitation, and mental and physical health recovery approaches. The research method used was library research, reviewing legislation, government policies, previous research results, and relevant literature discussing the integration of law and health in the context of drug abuse treatment. The results of the study show that the judicial system in Indonesia still tends to apply a retributive approach, even though Law No. 35 of 2009 has opened up opportunities for a rehabilitative approach through the principle of restorative justice. Meanwhile, health policies have offered solutions based on medical and social rehabilitation, but their implementation is still constrained by limited resources, infrastructure, and social stigma against addicts. Stronger integration between law enforcement agencies and the health system is needed to achieve fair, humane, and sustainable drug treatment, with a focus on comprehensive recovery for drug abusers.